The best of Girls to the rescue : tales of clever, courageous girls from around the world - Lansky, Bruce (Minnetonka, Minn. : Meadowbrook Press ; New York : Distributed by Simon & Schuster, 2002)
A collection of stories about girls and young women who don't sit around and wait for a prince to rescue them.
The fairy godmother's assistant / Bruce Lansky -- Troop 13 to the rescue / Penny Warner -- The clever daughter / Martha Johnson -- Liza and the lost letter / Bruce Lansky -- Keesha and the rat / J.M. Kelly -- Young Maid Marian and her amazing, astounding pig / Stephen Mooser -- Dingo trouble / Debra Tracy -- Kamal and the thieves / adapted by Bruce Lansky from an Indian folktale -- Fishing for trouble / Sandy Cudmore -- Grandma Rosa's bowl / adapted by Bruce Lansky from a Grimm Brothers' story -- Railroad through and through / Cynthia Mercati -- Sarah's pickle jar / adapted by Bruce Lansky from a Chinese folktale -- On the way to broken bow / Marianne J. Dyson -- Temper, temper / adapted by Bruce Lansky from an Italian folktale -- Tulia! / Joan Harries -- Kim's surprise witness / adapted by Bruce Lansky from a Chinese folktale -- For love of Sunny / Vivian Vande Velde -- Emily and the Underground Railroad / Joanne Mitchell -- Carla and the greedy merchant / adapted by Robert Scotellaro from a folktale -- Vassilisa the wise / adapted by Joanne Mitchell from a Russian fairytale -- Savannah's piglets / adapted by Sheryl L. Nelms from a folktale -- Shannon Holmes's first case / Stephen Mooser -- Maya's stone soup / adapted by Bruce Lansky from a European folktale -- The peacemakers / Lois Greiman -- The royal joust / Bruce Lansky.
Keywords: Girls -- Fiction; Short stories